Nano antibacterial agent composite mortar and preparation process thereof

By using copper chloride-coated silica and nanotitanium chloride as antibacterial agents in the composite mortar, combined with EVA emulsion and water reducing agent, the problem of degradation of the consistency and strength of the antibacterial composite mortar is solved, achieving efficient and long-lasting antibacterial effect and safety.

CN119683935APending Publication Date: 2025-03-25ANHUI JIT NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411858228.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

After the addition of antibacterial agents, the consistency, fluidity and strength of the existing antibacterial compound mortars have decreased, and some antibacterial agents are toxic and endanger the environment and human health.

Method used

Nanoantibacterial compound mortar is used to coat copper chloride with silica, combine nanotitanium chloride as antibacterial agent, and use EVA emulsion as a physical barrier, and combine water reducing agent and cellulose ether to maintain the consistency, adhesion and fluidity of the mortar.

Benefits of technology

It improves the antibacterial spectrum and antibacterial persistence, maintains the consistency, adhesion, strength and fluidity of the mortar, reduces the toxicity risk of antibacterial agents, and improves the safety and antibacterial effect of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683935A_ABST
    Figure CN119683935A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of composite mortar preparation, and discloses a nano antibacterial agent composite mortar, the nano antibacterial agent composite mortar comprises, by weight, 47.3% of cement, 47.3% of aggregate, 47.3% of a blending material, 47.3% of an additive, 47.3% of an antibacterial agent and 47.3% of a liquid material, the weight proportion of the aggregate accounts for 34.4% of the balance weight of the nano-antibacterial agent composite mortar, the weight proportion of the blending material accounts for 4.3% of the balance weight of the nano-antibacterial agent composite mortar, according to the nano-antibacterial agent composite mortar and the preparation technology, copper chloride is coated with silicon dioxide, and a silicon dioxide copper chloride coating is obtained; according to the present invention, the silicon dioxide copper chloride coating material and the nanometer titanium chloride are adopted as the antibacterial agent and are simultaneously added into the mortar, the EVA emulsion is adopted as the physical barrier so as to further improve the antibacterial spectrum and the antibacterial persistence, and the water reducing agent and the cellulose ether are adopted to compensate the influence of the silicon dioxide copper chloride coating material and the nanometer titanium chloride on the mortar so as to maintain the consistency, the cohesiveness, the strength and the fluidity of the mortar.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite mortar preparation, in particular to a nano antibacterial agent composite mortar and a preparation process thereof. Background Art

[0002] Composite mortar, also known as polymer mortar, refers to high-strength cement mortar mixed with modified epoxy emulsion or other modified copolymer emulsion. Composite mortar is generally used as soon as it is mixed.

[0003] The composite mortar in the prior art generally uses antibacterial composite mortar when facing high-standard environments, such as medical places, food processing places or household toilets. Antibacterial composite mortar is also a kind of composite mortar. Antibacterial composite mortar is compounded by adding antibacterial agent to mortar. By adding antibacterial agent to mortar, the mortar has antibacterial effect on the wall or floor after masonry, which can effectively reduce the growth of bacteria and improve the safety protection of medical, food and household use.

[0004] However, after the addition of antibacterial agents, the consistency and fluidity of the composite mortar will change. At the same time, with the addition of antibacterial agents, the compressive strength and bonding strength of the composite mortar will decrease, and it is very easy to crack during later use. After adding antibacterial agents, some antibacterial agents have certain toxicity. During the preparation process of mortar or during use, they will have a toxic effect on organisms in the environment and will also cause harm to human health. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a nano-antibacterial agent composite mortar and a preparation process, which solves the problems raised in the above background technology.

[0006] The present invention provides the following technical solution: a nano-antibacterial agent composite mortar, the nano-antibacterial agent composite mortar comprises cement, aggregate, admixture, admixture, antibacterial agent and liquid material;

[0007] Wherein, the weight ratio of the cement accounts for 47.3% of the weight of the nano antibacterial agent composite mortar;

[0008] Wherein, the weight ratio of the aggregate accounts for 34.4% of the weight of the nano antibacterial agent composite mortar;

[0009] Wherein, the weight ratio of the admixture material accounts for 4.3% of the weight of the nano antibacterial agent composite mortar;

[0010] Wherein, the weight ratio of the admixture accounts for 0.3% of the weight of the nano antibacterial agent composite mortar;

[0011] Wherein, the weight ratio of the antibacterial agent accounts for 0.4% of the weight of the nano antibacterial agent composite mortar;

[0012] The weight ratio of the liquid material is 13.3% of the weight of the nano-antibacterial agent composite mortar.

[0013] A nano-antibacterial agent composite mortar, wherein the cement is one of silicate cement, ordinary silicate cement or other high-strength cement.

[0014] A nano-antibacterial agent composite mortar, wherein the aggregate is one of fine sand, coarse sand or stone sand.

[0015] A nano-antibacterial agent composite mortar, wherein the admixture material is one of fly ash, slag powder or heavy calcium.

[0016] A nano-antibacterial agent composite mortar, wherein the admixture is one or more of a leveling agent, a plasticizer, a water reducer, a fiber reinforcement, an anti-cracking fiber or a cellulose ether.

[0017] A nano-antibacterial agent composite mortar, wherein the antibacterial agent is one or more of silver ions, cupric chloride, zinc oxide or nano-titanium chloride.

[0018] A nano-antibacterial agent composite mortar, wherein the liquid material is EVA emulsion and clean water.

[0019] A process for preparing a nano-antibacterial agent composite mortar is applicable to the preparation of any of the above-mentioned nano-antibacterial agent composite mortars, and the process comprises the following steps:

[0020] S1: Screen and pre-treat cement, aggregates and admixtures, select cement, aggregates and admixtures that meet quality standards, and clean and remove impurities from aggregates;

[0021] S2: Put cement, aggregate and admixture into a mixer according to the proportion for premixing. After the premixing is completed, add liquid material and admixture in order and mix them evenly.

[0022] S3: After the cement, aggregate, admixture, liquid material and admixture are mixed, the antibacterial agent is added in sequence, and then mixed at a high speed until the raw materials are evenly mixed and there are no obvious particles or lumps. The nano-antibacterial agent composite mortar is prepared.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The nano-antibacterial agent composite mortar and preparation process obtains a silica-copper chloride coating by coating cupric chloride with silica, and adds nano-titanium chloride as an antibacterial agent to the mortar at the same time, and uses EVA emulsion as a physical barrier to further improve the antibacterial spectrum and antibacterial sustainability. At the same time, a water reducer and a cellulose ether are used to compensate for the effect of the silica-copper chloride coating and nano-titanium chloride as antibacterial agents added to the mortar, so that the mortar can maintain the consistency, adhesion, strength and fluidity of the standard mortar after the silica-copper chloride coating and nano-titanium chloride are added. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The figure is a process diagram for preparing the nano antibacterial agent composite mortar of the present invention; DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Embodiment 1:

[0028] A nano-antibacterial agent composite mortar, the nano-antibacterial agent composite mortar comprises cement, aggregate, admixture, additive, antibacterial agent and liquid material, wherein the weight ratio of cement accounts for 47.3% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of aggregate accounts for 34.4% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of admixture accounts for 4.3% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of additive accounts for 0.3% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of antibacterial agent accounts for 0.4% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of liquid material accounts for 13.3% of the weight of the nano-antibacterial agent composite mortar;

[0029] The cement is one of silicate cement, ordinary silicate cement or other high-strength cement, the aggregate is one of fine sand, coarse sand or stone sand, the admixture is one of fly ash, slag powder or heavy calcium, the admixture is one of leveling agent, plasticizer, water reducer, fiber reinforcement, anti-cracking fiber or cellulose ether, the antibacterial agent is one of silver ion, copper chloride, zinc oxide or nano titanium chloride, and the liquid material is EVA emulsion and clean water;

[0030] Specifically, the cement is Portland cement, which weighs 550 kg;

[0031] The aggregate is stone sand, and its weight is 400kg;

[0032] The admixture material is heavy calcium, and its weight is 50kg;

[0033] The admixtures are water reducing agent and cellulose ether, and the weights thereof are 1.5 kg of water reducing agent and 2 kg of cellulose ether respectively;

[0034] The antibacterial agents are copper chloride and nano titanium chloride, and their weights are 2 kg of copper chloride and 3 kg of nano titanium chloride respectively;

[0035] The liquid materials are EVA emulsion and clean water, and their weights are 55kg of EVA emulsion and 100kg of clean water respectively;

[0036] Then, the above raw materials are processed and prepared according to the following process for the nano antibacterial agent composite mortar embodiment 1:

[0037] S1: Screening and pre-treating silicate cement, stone sand and heavy calcium carbonate to select silicate cement, stone sand and heavy calcium carbonate that meet the quality standards, wherein the strength grade selection standard of silicate cement includes but is not limited to 62.5 and 62.5R, wherein the particle size of stone sand is 0.15mm-5mm, and the particle size of heavy calcium carbonate is 5-15 microns, and mechanical screening is adopted, using a vibrating screen to screen out qualified stone sand and heavy calcium carbonate, and the qualified stone sand is put into a cleaning machine for cleaning to remove soil impurities, organic impurities and salt impurities on the surface of the stone sand, so as to avoid affecting the strength and adhesion of the nano-antibacterial agent composite mortar during preparation;

[0038] S2: Put silicate cement, stone sand and heavy calcium into a mixer according to a proportion and stir for 2 minutes at a stirring speed of 45 revolutions per minute, so that silicate cement, stone sand and heavy calcium are pre-mixed as powders. After the pre-mixing is completed, add EVA emulsion, water reducing agent, cellulose ether and clean water into the mixer in order, and then stir for 5 minutes at a stirring speed of 55 revolutions per minute; the fluidity of the mortar is improved by the water reducing agent, so that the mortar reaches the workability required for construction, and the water retention, thickening and adhesion of the mortar are further improved by the cellulose ether;

[0039] After EVA emulsion, water reducing agent, cellulose ether, clean water, silicate cement, stone sand and heavy calcium are fully mixed, a preliminary composite mortar is formed;

[0040] S3: After EVA emulsion, water reducer, cellulose ether, clean water, silicate cement, stone sand and heavy calcium are fully mixed, antibacterial agent is added in sequence, and the cupric chloride in the antibacterial agent is coated with silica in advance. The specific preparation process is to use a sol-gel method to coat the surface of cupric chloride with silica to form a coating layer, and then obtain a silica-copper chloride coating. The coating of cupric chloride with silica reduces the toxicity of direct release of cupric chloride, and also plays a role in slow release of cupric chloride, prolonging the antibacterial time of cupric chloride, reducing the harm to people and objects in the surrounding environment, and at the same time reducing the influence of light on cupric chloride, ensuring that the nano-titanium chloride has sufficient light, the silica-copper chloride coating can form a more stable synergistic antibacterial mechanism with the nano-titanium chloride, avoiding the mutual influence between the silica-copper chloride coating and the nano-titanium chloride;

[0041] Then, the nano titanium chloride is preferentially put into the mixer and stirred for 5 minutes at a stirring speed of 65 revolutions per minute. During the stirring process, clean water is continuously added to assist the mixing of the nano titanium chloride, thereby avoiding the agglomeration of the nano titanium chloride, allowing the nano titanium chloride to be more finely integrated into the composite mortar, so that the nano titanium chloride is first distributed in various positions of the composite mortar, providing a stable environment for the subsequent mixing of the silicon dioxide copper chloride coating;

[0042] Then, the silicon dioxide copper chloride coating is put into a mixer and stirred for 8 minutes at a stirring speed of 45 revolutions per minute. During the stirring process, clean water is continuously added to assist in better mixing of the silicon dioxide copper chloride coating. By reducing the rotation speed of the mixer, the wear of the silicon dioxide copper chloride coating is reduced, and the stability of the mixing of the silicon dioxide copper chloride coating and the composite mortar is improved. At the same time, the EVA emulsion and nano-titanium chloride that have been mixed in the composite mortar provide a stable environment for the mixing of the silicon dioxide copper chloride coating.

[0043] During the mixing process of the silica-copper chloride coating in the mixer, with the cooperation of the water reducer and the cellulose ether, the influence of the silica-copper chloride coating and the nano-titanium chloride on the mortar is reduced, and the silica-copper chloride coating and the nano-titanium chloride cause the consistency, adhesion, strength and fluidity of the mortar to be reduced. This ensures that the consistency, adhesion, strength and fluidity of the mortar are maintained while the antibacterial agent is added. After the raw materials are evenly mixed and there are no obvious particles and lumps, the preparation of the nano-antibacterial agent composite mortar is completed.

[0044] It should be noted that when preparing the nano-antibacterial agent composite mortar, clean water is in a state of continuous addition rather than a one-time addition, that is, when the EVA emulsion, water reducer, and cellulose ether are added to the mixer in sequence, clean water needs to be added; when the nano-titanium chloride is added to the mixer, clean water needs to be added; when the silicon dioxide copper chloride coating is added to the mixer, clean water needs to be added;

[0045] In the actual use process of the nano-antibacterial agent composite mortar after preparation, the physical barrier is formed by the EVA emulsion, which further reduces the release of cupric chloride toxic gas and improves the safety of the use of this product. At the same time, with the cooperation of the silica-copper chloride coating and nano-titanium chloride, the photocatalytic property can be effectively improved, that is, the silica-copper chloride coating can broaden the range of light absorption to a certain extent, so that the nano-titanium chloride absorbs more wavelengths of light and improves the utilization rate of solar energy. At the same time, the cooperation of the two forms a synergistic antibacterial mechanism, expands the antibacterial spectrum, and can inhibit bacteria more effectively, more lastingly and safely.

[0046] In summary, the antibacterial efficiency of the nano antibacterial agent composite mortar prepared in Example 1 is 94%.

[0047] Embodiment 2:

[0048] A nano-antibacterial agent composite mortar, the nano-antibacterial agent composite mortar comprises cement, aggregate, admixture, additive, antibacterial agent and liquid material, wherein the weight ratio of cement accounts for 43% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of aggregate accounts for 38.7% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of admixture accounts for 4.3% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of additive accounts for 0.3% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of antibacterial agent accounts for 0.4% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of liquid material accounts for 13.3% of the weight of the nano-antibacterial agent composite mortar;

[0049] The cement is one of silicate cement, ordinary silicate cement or other high-strength cement, the aggregate is one of fine sand, coarse sand or stone sand, the admixture is one of fly ash, slag powder or heavy calcium, the admixture is one of leveling agent, plasticizer, water reducer, fiber reinforcement, anti-cracking fiber or cellulose ether, the antibacterial agent is one of silver ion, copper chloride, zinc oxide or nano titanium chloride, and the liquid material is EVA emulsion and clean water;

[0050] Specifically, the cement is Portland cement, and its weight is 500 kg;

[0051] The aggregate is stone sand, and its weight is 450kg;

[0052] The blending material is heavy calcium, and its weight is 50kg;

[0053] The admixtures are water reducing agent and cellulose ether, and the weights thereof are 1.5 kg of water reducing agent and 2 kg of cellulose ether respectively;

[0054] The antibacterial agents are copper chloride and nano titanium chloride, and their weights are 2 kg of copper chloride and 3 kg of nano titanium chloride respectively;

[0055] The liquid materials are EVA emulsion and clean water, and their weights are 55kg of EVA emulsion and 100kg of clean water respectively;

[0056] Then, the above raw materials are processed and prepared according to the following process for the nano antibacterial agent composite mortar embodiment 2:

[0057] S1: Screening and pre-treating silicate cement, stone sand and heavy calcium carbonate to select silicate cement, stone sand and heavy calcium carbonate that meet the quality standards, wherein the strength grade selection standard of silicate cement includes but is not limited to 62.5 and 62.5R, wherein the particle size of stone sand is 0.15mm-5mm, and the particle size of heavy calcium carbonate is 5-15 microns, and mechanical screening is adopted, using a vibrating screen to screen out qualified stone sand and heavy calcium carbonate, and the qualified stone sand is put into a cleaning machine for cleaning to remove soil impurities, organic impurities and salt impurities on the surface of the stone sand, so as to avoid affecting the strength and adhesion of the nano-antibacterial agent composite mortar during preparation;

[0058] S2: Put silicate cement, stone sand and heavy calcium into a mixer according to a proportion and stir for 2 minutes at a stirring speed of 45 revolutions per minute, so that silicate cement, stone sand and heavy calcium are pre-mixed as powders. After the pre-mixing is completed, add EVA emulsion, water reducing agent, cellulose ether and clean water into the mixer in order, and then stir for 5 minutes at a stirring speed of 55 revolutions per minute; the fluidity of the mortar is improved by the water reducing agent, so that the mortar reaches the workability required for construction, and the water retention, thickening and adhesion of the mortar are further improved by the cellulose ether;

[0059] After EVA emulsion, water reducing agent, cellulose ether, clean water, silicate cement, stone sand and heavy calcium are fully mixed, a preliminary composite mortar is formed;

[0060] S3: After EVA emulsion, water reducer, cellulose ether, clean water, silicate cement, stone sand and heavy calcium are fully mixed, antibacterial agent is added in sequence, and the cupric chloride in the antibacterial agent is coated with silica in advance. The specific preparation process is to use a sol-gel method to coat the surface of cupric chloride with silica to form a coating layer, and then obtain a silica-copper chloride coating. The coating of cupric chloride with silica reduces the toxicity of direct release of cupric chloride, and also plays a role in slow release of cupric chloride, prolonging the antibacterial time of cupric chloride, reducing the harm to people and objects in the surrounding environment, and at the same time reducing the influence of light on cupric chloride, ensuring that the nano-titanium chloride has sufficient light, the silica-copper chloride coating can form a more stable synergistic antibacterial mechanism with the nano-titanium chloride, avoiding the mutual influence between the silica-copper chloride coating and the nano-titanium chloride;

[0061] Then, the nano titanium chloride is preferentially put into the mixer and stirred for 5 minutes at a stirring speed of 65 revolutions per minute. During the stirring process, clean water is continuously added to assist the mixing of the nano titanium chloride, thereby avoiding the agglomeration of the nano titanium chloride, allowing the nano titanium chloride to be more finely integrated into the composite mortar, so that the nano titanium chloride is first distributed in various positions of the composite mortar, providing a stable environment for the subsequent mixing of the silicon dioxide copper chloride coating;

[0062] Then, the silicon dioxide copper chloride coating is put into a mixer and stirred for 8 minutes at a stirring speed of 45 revolutions per minute. During the stirring process, clean water is continuously added to assist in better mixing of the silicon dioxide copper chloride coating. By reducing the rotation speed of the mixer, the wear of the silicon dioxide copper chloride coating is reduced, and the stability of the mixing of the silicon dioxide copper chloride coating and the composite mortar is improved. At the same time, the EVA emulsion and nano-titanium chloride that have been mixed in the composite mortar provide a stable environment for the mixing of the silicon dioxide copper chloride coating.

[0063] During the mixing process of the silica-copper chloride coating in the mixer, with the cooperation of the water reducer and the cellulose ether, the influence of the silica-copper chloride coating and the nano-titanium chloride on the mortar is reduced, and the silica-copper chloride coating and the nano-titanium chloride cause the consistency, adhesion, strength and fluidity of the mortar to be reduced. This ensures that the consistency, adhesion, strength and fluidity of the mortar are maintained while the antibacterial agent is added. After the raw materials are evenly mixed and there are no obvious particles and lumps, the preparation of the nano-antibacterial agent composite mortar is completed.

[0064] It should be noted that when preparing nano-antibacterial agent composite mortar, clean water is in a state of continuous addition rather than a one-time addition, that is, clean water needs to be added when EVA emulsion, water reducer and cellulose ether are added to the mixer in sequence; clean water needs to be added when nano-titanium chloride is added to the mixer; and clean water needs to be added when the silica-copper chloride coating is added to the mixer.

[0065] In summary, the antibacterial efficiency of the nano-antibacterial agent composite mortar prepared in Example 2 is 86%.

[0066] Embodiment three:

[0067] A nano-antibacterial agent composite mortar, the nano-antibacterial agent composite mortar comprises cement, aggregate, admixture, additive, antibacterial agent and liquid material, wherein the weight ratio of cement accounts for 38.7% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of aggregate accounts for 43% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of admixture accounts for 4.3% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of additive accounts for 0.3% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of antibacterial agent accounts for 0.4% of the weight of the nano-antibacterial agent composite mortar, wherein the weight ratio of liquid material accounts for 13.3% of the weight of the nano-antibacterial agent composite mortar;

[0068] The cement is one of silicate cement, ordinary silicate cement or other high-strength cement, the aggregate is one of fine sand, coarse sand or stone sand, the admixture is one of fly ash, slag powder or heavy calcium, the admixture is one of leveling agent, plasticizer, water reducer, fiber reinforcement, anti-cracking fiber or cellulose ether, the antibacterial agent is one of silver ion, copper chloride, zinc oxide or nano titanium chloride, and the liquid material is EVA emulsion and clean water;

[0069] Specifically, the cement is Portland cement, which weighs 450 kg;

[0070] The aggregate is stone sand, and its weight is 500kg;

[0071] The admixture material is heavy calcium, and its weight is 50kg;

[0072] The admixtures are water reducing agent and cellulose ether, and the weights thereof are 1.5 kg of water reducing agent and 2 kg of cellulose ether respectively;

[0073] The antibacterial agents are copper chloride and nano titanium chloride, and their weights are 2 kg of copper chloride and 3 kg of nano titanium chloride respectively;

[0074] The liquid materials are EVA emulsion and clean water, and their weights are 55kg of EVA emulsion and 100kg of clean water respectively;

[0075] Then, the above raw materials were processed and prepared according to the following process for the nano antibacterial agent composite mortar embodiment 3:

[0076] S1: Screening and pre-treating silicate cement, stone sand and heavy calcium carbonate to select silicate cement, stone sand and heavy calcium carbonate that meet the quality standards, wherein the strength grade selection standard of silicate cement includes but is not limited to 62.5 and 62.5R, wherein the particle size of stone sand is 0.15mm-5mm, and the particle size of heavy calcium carbonate is 5-15 microns, and mechanical screening is adopted, using a vibrating screen to screen out qualified stone sand and heavy calcium carbonate, and the qualified stone sand is put into a cleaning machine for cleaning to remove soil impurities, organic impurities and salt impurities on the surface of the stone sand, so as to avoid affecting the strength and adhesion of the nano-antibacterial agent composite mortar during preparation;

[0077] S2: Put silicate cement, stone sand and heavy calcium into a mixer according to a proportion and stir for 2 minutes at a stirring speed of 45 revolutions per minute, so that silicate cement, stone sand and heavy calcium are pre-mixed as powders. After the pre-mixing is completed, add EVA emulsion, water reducing agent, cellulose ether and clean water into the mixer in order, and then stir for 5 minutes at a stirring speed of 55 revolutions per minute; the fluidity of the mortar is improved by the water reducing agent, so that the mortar reaches the workability required for construction, and the water retention, thickening and adhesion of the mortar are further improved by the cellulose ether;

[0078] After EVA emulsion, water reducing agent, cellulose ether, clean water, silicate cement, stone sand and heavy calcium are fully mixed, a preliminary composite mortar is formed;

[0079] S3: After EVA emulsion, water reducer, cellulose ether, clean water, silicate cement, stone sand and heavy calcium are fully mixed, antibacterial agent is added in sequence, and the cupric chloride in the antibacterial agent is coated with silica in advance. The specific preparation process is to use a sol-gel method to coat the surface of cupric chloride with silica to form a coating layer, and then obtain a silica-copper chloride coating. The coating of cupric chloride with silica reduces the toxicity of direct release of cupric chloride, and also plays a role in slow release of cupric chloride, prolonging the antibacterial time of cupric chloride, reducing the harm to people and objects in the surrounding environment, and at the same time reducing the influence of light on cupric chloride, ensuring that the nano-titanium chloride has sufficient light, the silica-copper chloride coating can form a more stable synergistic antibacterial mechanism with the nano-titanium chloride, avoiding the mutual influence between the silica-copper chloride coating and the nano-titanium chloride;

[0080] Then, the nano titanium chloride is preferentially put into the mixer and stirred for 5 minutes at a stirring speed of 65 revolutions per minute. During the stirring process, clean water is continuously added to assist the mixing of the nano titanium chloride, thereby avoiding the agglomeration of the nano titanium chloride, allowing the nano titanium chloride to be more finely integrated into the composite mortar, so that the nano titanium chloride is first distributed in various positions of the composite mortar, providing a stable environment for the subsequent mixing of the silicon dioxide copper chloride coating;

[0081] Then, the silicon dioxide copper chloride coating is put into a mixer and stirred for 8 minutes at a stirring speed of 45 revolutions per minute. During the stirring process, clean water is continuously added to assist in better mixing of the silicon dioxide copper chloride coating. By reducing the rotation speed of the mixer, the wear of the silicon dioxide copper chloride coating is reduced, and the stability of the mixing of the silicon dioxide copper chloride coating and the composite mortar is improved. At the same time, the EVA emulsion and nano-titanium chloride that have been mixed in the composite mortar provide a stable environment for the mixing of the silicon dioxide copper chloride coating.

[0082] During the mixing process of the silica-copper chloride coating in the mixer, with the cooperation of the water reducer and the cellulose ether, the influence of the silica-copper chloride coating and the nano-titanium chloride on the mortar is reduced, and the silica-copper chloride coating and the nano-titanium chloride cause the consistency, adhesion, strength and fluidity of the mortar to be reduced. This ensures that the consistency, adhesion, strength and fluidity of the mortar are maintained while the antibacterial agent is added. After the raw materials are evenly mixed and there are no obvious particles and lumps, the preparation of the nano-antibacterial agent composite mortar is completed.

[0083] It should be noted that when preparing nano-antibacterial agent composite mortar, clean water is in a state of continuous addition rather than a one-time addition, that is, clean water needs to be added when EVA emulsion, water reducer and cellulose ether are added to the mixer in sequence; clean water needs to be added when nano-titanium chloride is added to the mixer; and clean water needs to be added when the silica-copper chloride coating is added to the mixer.

[0084] In summary, the antibacterial efficiency of the nano-antibacterial agent composite mortar prepared in Example 3 is 82%. By comparison, the nano-antibacterial agent composite mortar prepared in Example 1 has the best antibacterial effect.

[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A nano-antibacterial agent composite mortar, characterized in that: The nano antibacterial agent composite mortar comprises cement, aggregate, admixture, admixture, antibacterial agent and liquid material; Wherein, the weight ratio of the cement accounts for 47.3% of the weight of the nano antibacterial agent composite mortar; Wherein, the weight ratio of the aggregate accounts for 34.4% of the weight of the nano antibacterial agent composite mortar; Wherein, the weight ratio of the admixture material accounts for 4.3% of the weight of the nano antibacterial agent composite mortar; Wherein, the weight ratio of the admixture accounts for 0.3% of the weight of the nano antibacterial agent composite mortar; Wherein, the weight ratio of the antibacterial agent accounts for 0.4% of the weight of the nano antibacterial agent composite mortar; The weight ratio of the liquid material is 13.3% of the weight of the nano-antibacterial agent composite mortar.

2. The nano-antibacterial agent composite mortar according to claim 1, characterized in that: The cement is one of silicate cement, ordinary silicate cement or other high-strength cement.

3. The nano-antibacterial agent composite mortar according to claim 1, characterized in that: The aggregate is one of fine sand, coarse sand or stone sand.

4. The nano-antibacterial agent composite mortar according to claim 1, characterized in that: The admixture material is one of fly ash, slag powder or heavy calcium.

5. The nano-antibacterial agent composite mortar according to claim 1, characterized in that: The additive is one or more of a leveling agent, a plasticizer, a water reducing agent, a fiber reinforcing agent, an anti-cracking fiber or a cellulose ether.

6. The nano-antibacterial agent composite mortar according to claim 1, characterized in that: The antibacterial agent is one or more of silver ions, copper chloride, zinc oxide or nano titanium chloride.

7. The nano-antibacterial agent composite mortar according to claim 1, characterized in that: The liquid material is EVA emulsion and clean water.

8. A preparation process of nano antibacterial agent composite mortar, characterized in that: The process is applicable to the preparation of the nano antibacterial agent composite mortar according to any one of claims 1 to 7, and comprises the following steps: S1: Screen and pre-treat cement, aggregates and admixtures, select cement, aggregates and admixtures that meet quality standards, and clean and remove impurities from aggregates; S2: Put cement, aggregate and admixture into a mixer according to the proportion for premixing. After the premixing is completed, add liquid material and admixture in order and mix them evenly. S3: After the cement, aggregate, admixture, liquid material and admixture are mixed, the antibacterial agent is added in sequence, and then mixed at a high speed until the raw materials are evenly mixed and there are no obvious particles or lumps. The nano-antibacterial agent composite mortar is prepared.